The proactive health behavior and somatic functional status in Chinese rural chronic patients: the mediating effects of social participation - Huang, Yangzhen; Qing, Hua; Pan, Yangyang; Wang, Chunying; Dong, Heng; Song, Jia; Zhang, Kangkang; Wei, Yilin; Tang, Shangfeng; Zhang, Min (Frontiers in Public Health, 2025)
BackgroundAs chronic diseases become more prevalent in rural China, maintaining health and functional capacity has become a major challenge. In this context, individual proactive health behaviors (PHB) may play a crucial role. However, the mechanisms through which PHB influence somatic functional status (SFS) are still unclear. Particularly, the role of social participation (SP) in this process remains unexplored.MethodsA cross-sectional survey was conducted among 3,295 chronic disease patients in rural China. Data on PHB and SFS was evaluated using validated Likert scales. Data on SP were collected using a binary-response questionnaire covering seven domains of activity. Descriptive statistics were used to characterize the sample demographics and the distributions of key variables. Hierarchical regression analysis was performed to test the mediation effects.ResultsThe mean scores for participants were 24.98 ± 5.89 for PHB, 2.22 ± 1.21 for SP, and 43.33 ± 10.00 for SFS. Significant correlations were found between PHB and SP (r = 0.21, p < 0.001), SP and SFS (r = 0.23, p < 0.001), and PHB and SFS (r = 0.11, p < 0.001). Hierarchical regression and bootstrap analyses confirmed that SP partially mediated the relationship between PHB and SFS, explaining 42.01% of the total effect.ConclusionAmong rural patients with chronic diseases in China, individual health proactivity primarily enhances somatic function by promoting social participation. Therefore, integrated interventions that encourage both proactive health behaviors and social participation are recommended. These interventions can optimize chronic disease management outcomes in this population.